Generating Novel Aroma Phenotypes Using Commercial Wine Samples to Characterize an F1 Population - Awale, Mani; Liu, Connie; Kwasniewski, Misha T. (Frontiers in Plant Science, 2022)
Due to their disease tolerance and cold hardy nature, interspecific hybrid grapes are widely grown in the Midwestern and Northeastern United States, with additional interest worldwide in the face of increased abiotic and biotic stresses from climate change. However, the aroma profile of these hybrids are unique and generally less popular in comparison to Vitis. vinifera grapes. One of the challenges in any phenotyping project is first defining the traits of interest. As wine quality was the ultimate metric of interest, the aroma profile of commercial wines produced from the parents of a breeding population (V. aestivalis derived ‘Norton’ x V. vinifera. ‘Cabernet Sauvignon’) were first assessed for traits of interest. We investigated 11 commercial wines each of Norton, a popular hybrid in Missouri and Cabernet Sauvignon (Cab) for their volatile profiles using the more inclusive metabolomics-based approach. We then analyzed 21 Norton and 21 Cab grapes for the free and bound volatile compounds using HS-SPME-GCMS to validate the differences in wine. The GCMS data was processed using XCMS to find features that different between the two cultivars. The two cultivars were found to have differences in their volatile profiles, with 304 features different for wine volatiles, 418 features different for free volatiles, and 302 features different for bound volatiles at 0.05 significance level and with at least a 1.5-fold change between the two cultivars. Those features were used to identify several odor active compounds in both grapes and wines, including β-Damascenone, β-Ionone, Eugenol, TDN, Ethyl hexadecanoate, and Methyl salicylate. Some of the identified compounds were higher in Norton than Cab, however, several features were higher in Cab. Using the identified aroma compounds as markers, we phenotyped an F1 population of Norton and Cab. The F1 population was found to be segregating for many aroma compounds with some genotypes demonstrating an even higher concentration of aroma volatiles than either of the parents. Ultimately, using commercially available samples paired with untargeted analysis proved to be an efficient way to determine phenotypes of interest for further analysis and may offer an easy way to choose potential parents with desired traits for breeding.